Implementation Monitoring of a Promotora-Led, Home-Based Obesity Prevention Pilot Study With Latino Preschool Children and Their Mothers. (July 2021) - Taverno Ross, Sharon E.; Smith Tapia, Ivonne; Saunders, Ruth P.; Documet, Patricia I.; Pate, Russell R.
Background: Latino preschool children have higher rates of obesity than children from other racial/ethnic backgrounds. Few effective, culturally-tailored obesity prevention interventions exist that have focused on Latino preschool children, and even fewer have published results of the process evaluation. The purpose of this paper was to monitor reach, fidelity, and completeness of implementation to determine whether ANDALE, a promising promotora -led, home-based pilot study to prevent obesity in Latino preschool children, was implemented as planned. Methods: Guided by a logic model, we assessed reach, implementation fidelity and completeness through descriptive analyses of multiple data sources. Reach was assessed through attendance records. Fidelity was assessed via observation checklist and completeness was assessed via survey with both parents and promotoras in a subsample of 12 families. Results: Promotoras recruited participants primarily through their own social networks and delivered the intervention to 50 families (mother-child dyads); the majority were of Mexican-origin, low-acculturation, dual-parent households. Nearly all (98%) families completed the whole 10-week intervention. Results demonstrated completeness and fidelity of implementation were acceptable in a subsample of 12 families. In sum, 75% of families in the subsample met the criteria (≥75%) for overall implementation of essential program elements (i.e., reach, completeness, and fidelity). Conclusion: Evidence suggests that ANDALE was delivered with high levels of completeness and fidelity in this sample of Latino families with preschool-aged children. These results support implementation of ANDALE in a large, randomized trial.